INDIVIDUAL-LEVEL DETERMINANTS AND CLINICAL OUTCOMES OF HEAD ACCELERATION EVENT EXPOSURE IN YOUTH ICE HOCKEY - Swenson, Abigail Glazier (Wake Forest University, 2025)
Ice hockey is an increasingly popular collision sport, with almost 1 million participants under the age of 20 across the globe. Boys’ and men’s ice hockey is characterized by body checking, intentional player-to-player collisions that aim to disrupt an opponent’s control of the puck. Concussion has been a long-standing concern in ice hockey, though most player-to-player contact does not result in diagnosable injury. However, an increasing number of studies in ice hockey and other contact and collision sports have reported a relationship between repetitive head acceleration event (HAE) exposure and negative health outcomes, both acutely and later in life. A wide body of work has investigated environmental and gameplay features of ice hockey contributing to HAE exposure, but it is less well-understood how intrinsic factors influence athletes’ HAE frequency or magnitude. The limited insight into individual-level determinants of ice hockey HAE exposure and still-developing understanding of HAE exposure’s role on clinical outcomes necessitates a need for additional study. Better understanding of determinants and outcomes of HAE exposure will facilitate opportunities for interventions to reduce exposure and improve ice hockey safety. This dissertation aims to evaluate individual-level preseason physical performance as a potential determinant of HAE exposure and to characterize temporal change in measures of neurobehavioral health as outcomes of HAE exposure among a sample of boys’ youth ice hockey athletes. Findings may add to a growing body of literature on determinants and clinical outcomes of HAE exposure, driving future interventions to reduce exposure and mitigate risk of negative health outcomes associated with contact and collision sport participation.This research is comprised of three parts: 1. Part 1 investigates individual-level physical performance as a novel determinant of ice hockey HAE exposure among a sample of boys’ youth ice hockey athletes. 2. Part 2 evaluates relationships between ice hockey HAE exposure and postural control outcomes and compares postural control between ice hockey athletes and a group of age-matched non-contact sport athlete controls. 3. Part 3 assesses relationships between ice hockey HAE exposure and another measure of neurobehavioral health – neurocognition; temporal changes in neurocognition were additionally assessed between ice hockey and control groups.
Keywords: Functional outcomes; Head impact biomechanics; Ice hockey; Neurocognition; Postural control; Sport performance